68Ga-DOTANOC PET/CT in Adrenal Schwannoma. (January 2023) - Aggarwal, Piyush; Singh, Harmandeep; Kumar, Rajender; Nada, Ritambhra; Bora, Girdhar S.; Walia, Rama
Abstract: Adrenal schwannoma is a rare adrenal incidentaloma. It is a benign tumor arising from the Schwann cells. Differentiating benign from malignant adrenal lesions requires a combination of clinical, biochemical, imaging, and histopathological findings. 68 Ga-DOTANOC PET/CT is one of the sensitive imaging modalities to detect adrenal lesions such as pheochromocytoma. Multiple benign and malignant lesions show somatostatin receptor expression causing a high probability of false-positive findings on somatostatin receptor imaging. We present a case of adrenal incidentaloma positive on 68 Ga-DOTANOC PET, which revealed a benign adrenal spindle cell tumor on histopathology.